D-Dimer Levels are Significantly Increased in Blood Taken From Varicose Veins Compared With Antecubital Blood From the Same Patient. (October 2015) - Lattimer, Christopher R.; Kalodiki, Evi; Geroulakos, George; Syed, Daneyal; Hoppensteadt, Debra; Fareed, Jawed
D -Dimer is a prothrombotic biomarker and a very sensitive measure of endogenous fibrinolysis. It is used as a screening test for suspected deep vein thrombosis. This study investigated whetherd -dimer levels were increased in the varicose veins of patients in comparison to their own arm samples. Patients, n = 24, 17 male, age 45 (25-91), C2-6, awaiting saphenous laser ablation were compared to matched controls, n = 24, 17 male, age 42 (24-89). Concurrent venous blood samples were taken from the arm and a lower calf/ankle (varicose) vein. The median (interquartile range)d -dimer (ng/mL) level was significantly greater in the ankle than in the arm blood of the same patient at 319 (164-631) versus 281 (167-562), P = .003, Wilcoxon. This did not occur in the controls at 269 (80-564) versus 262 (106-526), P = .361, Wilcoxon. The results indicate increased endogenous fibrinolysis in varicose veins compared with arm blood. This suggests there is more thrombotic activity or dissolution of formed subclinical fibrin thrombus which may explain the association of varicose veins with superficial vein thrombosis. This contrasts with earlier studies reporting a local reduction in fibrinolysis in venous disease.